Determining Factors of Corporate Governance in Women Corporative of East Java Indonesia - Eni Wuryani; Merlyana Dwinda Yanthi (AKRUAL: JURNAL AKUNTANSI, 2020)
All over the world want organizations to be sustainable, like organizations in Indonesia. Corporate governance (CG) implementation is a must in an organization. The application of corporate governance in Indonesia is applied to organizations in the form of cooperatives. The study aimed to determine factors of corporate governance in women corporative of East Java, Indonesia. Factors that include corporate governance are internal control, the rules for members, annual member meetings. The object of this study was 159 Cooperatives in East Java, Indonesia. The implementation of coporate governance in women's cooperatives has been going well, judging by the cooperative's performance appraisal. The implementation of internal control still needs to be improved. Cooperative members have mostly fulfilled their obligations as members through payment of basic contributions and mandatory contributions. The meeting held by members of most women's cooperatives was carried out on time. Cooperatives are microfinance institutions for cooperative members. Cooperatives are organizations that are established for the welfare of members. Implementation of corporate governance in women's cooperatives will improve cooperative performance.